Activities of the Government of the Ukrainian State in 1918 in Solving the Issue of Unemployment in the Context of Social Exclusion: Structural and Organizational Aspect - KHOMENKO, Olena (Theoretical and Practical Research in Economic Fields; Vol 15 No 2 (2024): TPREF, Volume XV, Issue 2(30), Summer 2024, Special Issue, 2024)
The purpose of this study is to examine archival materials and historical experience in the fight against unemployment in 1918. To achieve this goal, the following methods were used: archival, statistical, historical, and hermeneutical methods. During the study, various archival data were analysed, which allowed creating an objective and comprehensive picture of social exclusion in a particular period. Additionally, unemployment statistics were reviewed, which revealed a high level of unemployment during the study period. The analysis of historical documents related to the government’s activities during this period led to the conclusion that Pavlo Skoropadskyi and his government took various measures to improve the situation. The Cabinet of Ministers of 1918 created new committees and exchanges aimed at addressing the problems of social exclusion and the economic situation of the population. The study of historical and policy documents for 1918 revealed that their effect was ambivalent, causing both positive and negative aspects in society. On the one hand, the committees helped to overcome social exclusion and stabilize the economic situation by promoting the development of new industries and markets. On the other hand, some measures may have caused negative reactions and conflicts in society, leading to some tension and uncertainty about the country’s future development path.